The impact of Syrian refugees on natives' labor market outcomes in Turkey: Evidence from a quasi-experimental design - Evren Ceritoglu; H. Burcu Gurcihan Yunculer; Huzeyfe Torun; Semih Tumen (IZA Journal of Labor Policy, 2017)
Civil conflict in Syria, started in March 2011, led to a massive wave of forced immigration from Northern Syria to the Southeastern regions of Turkey, which later had serious economic/political repercussions on the MENA region and most of Europe. This paper exploits this natural experiment to estimate the impact of Syrian refugees on the labor market outcomes of natives in Turkey. Using a difference-in-differences strategy, we find that immigration has considerably affected the employment outcomes of natives, while its impact on wage outcomes has been negligible. We document notable employment losses among informal workers as a consequence of refugee inflows. Formal employment increased slightly potentially due to increased social services in the region. The majority of those who lost their informal jobs have either left the labor force or remained unemployed. Formal employment and unemployment rates have increased, while labor force participation, informal employment, and job finding rates have declined among natives. Disadvantaged groups, i.e., women, younger workers, and less-educated workers, have been affected the worst. The prevalence of informal employment in the Turkish labor markets has amplified the negative impact of Syrian refugee inflows on natives' labor market outcomes. Overall, the impact of Syrian refugee inflows on the Turkish labor markets has been limited, which suggests that the potential costs on the European and other affected labor markets might also be limited.
Keywords: J15; J21; J46; J61; C21; 330; Syrian civil war; Immigration; Turkey; Labor market; Informality; Difference in differences; Bürgerkrieg; Einwanderung; Arbeitsmarkt; Informelle Wirtschaft; Syrien; Türkei